Carbon Dioxide, Energy Fluxes And Evapotranspiration Of The Oil Palm Canopy On Mineral Soil - Ibrahim, Anis Suriani (2019)
The research work focuses on the measurements of carbon dioxide flux, en-ergy fluxes and evapotranspiration of the oil palm canopy for oil palm trees planted on mineral soil. The first aim of this research is to assess the responses of the oil palm canopy (in terms of carbon dioxide flux) to changes in meteorology and season while the second aim is to assess the performance of the evapotranspiration models (Penman-Monteith and Bowen Ratio Energy Balance) for the oil palm canopy. The sampling was conducted over a 25-month period using 30-min averaging time of eddy covariance method in Keratong, Pahang. Results show that the oil palm is very productive tropical C3 plant in which it assimilates 4.3 μmol m–2 s–1 (60 t ha–1 yr–1) of carbon dioxide from the atmosphere. The monsoonal (the Northeast and South-west monsoons) and the diurnal variations of carbon dioxide flux, energy flux and evapotranspiration exhibit notable patterns. On the monsoonal timescale, the varia-tions in the net radiation and the vapour pressure deficit leads to the increase in car-bon dioxide assimilations. The vapour pressure deficit threshold for the stomata was also observed to be >2000 Pa and >1000 Pa for the Southwest and Northeast mon-soons, respectively. The evapotranspiration models’ performance analyses show that the Penman-Monteith model tend to underestimate the actual evapotranspiration by 2% while the Bowen Ratio Energy Balance model overestimate actual evapotranspi-ration by 17%.